The significance of the episodic nature of atmospheric deposition to Low Nutrient Low Chlorophyll regions. Issue 11 (10th November 2014) - Guieu, C.; Aumont, O.; Paytan, A.; Bopp, L.; Law, C. S.; Mahowald, N.; Achterberg, E. P.; Marañón, E.; Salihoglu, B.; Crise, A.; Wagener, T.; Herut, B.; et al.
Abstract In the vast Low Nutrient Low‐Chlorophyll (LNLC) Ocean, the vertical nutrient supply from the subsurface to the sunlit surface waters is low, and atmospheric contribution of nutrients may be one order of magnitude greater over short timescales. The short turnover time of atmospheric Fe and N supply (<1 month for nitrate) further supports deposition being an important source of nutrients in LNLC regions. Yet, the extent to which atmospheric inputs are impacting biological activity and modifying the carbon balance in oligotrophic environments has not been constrained. Here, we quantify and compare the biogeochemical impacts of atmospheric deposition in LNLC regions using both a compilation of experimental data and model outputs. A metadata‐analysis of recently conducted field and laboratory bioassay experiments reveals complex responses, and the overall impact is not a simple "fertilization effect of increasing phytoplankton biomass" as observed in HNLC regions. Although phytoplankton growth may be enhanced, increases in bacterial activity and respiration result in weakening of biological carbon sequestration. The application of models using climatological or time‐averaged non‐synoptic deposition rates produced responses that were generally much lower than observed in the bioassay experiments. We demonstrate that experimental data and model outputs show better agreement on short timescale (days to weeks) when strong synoptic pulse of aerosols deposition, similar in magnitude to those observed in the field and introduced in bioassay experiments, is superimposed over the mean atmospheric deposition fields. These results suggest that atmospheric impacts in LNLC regions have been underestimated by models, at least at daily to weekly timescales, as they typically overlook large synoptic variations in atmospheric deposition and associated nutrient and particle inputs. Inclusion of the large synoptic variability of atmospheric input, and improved representation and parameterization of key processes that respond to atmospheric deposition, is required to better constrain impacts in ocean biogeochemical models. This is critical for understanding and prediction of current and future functioning of LNLC regions and their contribution to the global carbon cycle.